Assessing International Heritage Tourist Satisfaction in India - Srivastava, Manish (Indian Journal of Marketing, 2009)
Tourism industry today is one of the world’s fastest growing industries. India with its glorious past has ensured that the present and subsequent generations have plenty of historical and cultural heritages to be proud of. Tourism Industry is playing a vital role in the GDP of Indian Economy. Every year a lot of tourists come in India. Indian Government, with all its efforts tries to satisfy these tourists. This paper is an attempt to understand the satisfaction indicator among International Travelers relating to the heritage sites of India. A detailed study has been done on the basis of primary as well as secondary data. Secondary data was collected from journals, books, magazines, Internet as well as government agencies, whereas primary data was collected through brief, on-site interviews based on a structured, non-disguised questionnaire. The study shows that the satisfaction level of tourists in India is 5.72 in the scale of 10. This data was further analyzed on different factors and researcher tried to find out the impact of various factors on overall tourist satisfaction. The satisfaction was also analyzed gender wise, which gave an idea that overall women are more satisfied than men. Through this research paper researcher tries to find out the factors which is crucial for the success of tourist destinations and their positioning. The researcher also tries to find out the status of these factors in India and suggested some measures which can be utilized for up gradation of tourism Industry in India.